2004
DOI: 10.1002/cm.10168
|View full text |Cite
|
Sign up to set email alerts
|

A subclass of myosin XI is associated with mitochondria, plastids, and the molecular chaperone subunit TCP‐1α in maize

Abstract: The role and regulation of specific plant myosins in cyclosis is not well understood. In the present report, an affinity-purified antibody generated against a conserved tail region of some class XI plant myosin isoforms was used for biochemical and immunofluorescence studies of Zea mays. Myosin XI co-localized with plastids and mitochondria but not with nuclei, the Golgi apparatus, endoplasmic reticulum, or peroxisomes. This suggests that myosin XI is involved in the motility of specific organelles. Myosin XI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 73 publications
0
52
1
Order By: Relevance
“…Roles for class V myosins have also been revealed in the movement of the vacuole, Golgi, and ER elements (38). Strikingly, although no localization within the Golgi apparatus or ER was reported for maize myosin XI in a recent study (39), the same antibodies, generated against a conserved tail region of several isoforms, colocalized with plastids and mitochondria. The reduction in cytoplasmic streaming observed in mya2-1 plants indicates that this myosin class is involved in the motility of higher plant organelles and vesicles and, because of its size-dependent manner, argues for a specific function in the movement of large structures apparently corresponding to the mobile ER of the endoplasm.…”
Section: Involvement In Organelle Movement During Cytoplasmic Streamingmentioning
confidence: 95%
“…Roles for class V myosins have also been revealed in the movement of the vacuole, Golgi, and ER elements (38). Strikingly, although no localization within the Golgi apparatus or ER was reported for maize myosin XI in a recent study (39), the same antibodies, generated against a conserved tail region of several isoforms, colocalized with plastids and mitochondria. The reduction in cytoplasmic streaming observed in mya2-1 plants indicates that this myosin class is involved in the motility of higher plant organelles and vesicles and, because of its size-dependent manner, argues for a specific function in the movement of large structures apparently corresponding to the mobile ER of the endoplasm.…”
Section: Involvement In Organelle Movement During Cytoplasmic Streamingmentioning
confidence: 95%
“…Antibodies against a conserved Myosin XI peptide label the plasma membrane and maybe mitochondria . Recently, a subclass of Myosin XI has been shown to be associated with mitochondria and plastids (Wang and Pesacreta, 2004). Obviously, polypeptide-specific probes are needed to distinguish individual Myosin XIs in order to reveal their specific intracellular localization patterns.…”
Section: Seventeen Arabidopsis Myosinsmentioning
confidence: 99%
“…Immunolocalization studies indicated that myosin XIs are associated with various particles in lily (Lilium longiflorum) and tobacco (Nicotiana tabacum) pollen tubes (Yokota et al, 1995), with mitochondria, plastids, and lowdensity membranes in maize (Zea mays) root cells (Liu et al, 2001;Wang and Pesacreta, 2004), and with endoplasmic reticulum (ER) in tobacco BY2 cells . Specific antibodies against MYA2 showed that it is associated with peroxisomes in epidermal and guard cells of Arabidopsis leaves (Hashimoto et al, 2005).…”
mentioning
confidence: 99%